(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess quality of life and describe the current status of mental health problems among patients with dermatological conditions. Methods: A cross-sectional descriptive study was conducted in 2025 among 118 patients with dermatological diseases in Long Hiep commune, Vinh Long province. The study employed DLQI scale to evaluate quality of life and DASS-21 scale to assess patients’ mental health status. Results: The mean quality of life score was 3.2 ± 3.7 (indicating a small effect); however, 57.6% of patients experienced some degree of impairment. The prevalence of anxiety, depression, and stress was 17.8%, 16.1%, and 0.8%, respectively (with 100% of depression cases classified as moderate). Lesions located on the face and pruritus showed strong positive correlations with quality of life scores, anxiety, and depression (p < 0.001). Notably, age was inversely correlated with depression (r = -0.312), whereas stress was associated with urticaria and older age groups (r = 0.275). Conclusions: Dermatological diseases impose a heterogeneous psychological burden that varies significantly by age and lesion location. Psychological screening should be prioritized for younger patients, while greater emphasis should be placed on controlling physical symptoms among older adults.